Triglyceride glucose index and renal function decline in Han Chinese hypertensive patients - Hung‐Chang Chen; Yun‐Hsuan Tsai; Chin‐Chou Huang (The Journal of Clinical Hypertension, 2023)
Abstract Elevated triglyceride glucose (TyG) index is associated with an increased risk of cardiovascular disease. The current study aimed to investigate whether the TyG index was correlated with renal function decline in patients with hypertension. Han Chinese participants with essential hypertension were included. The TyG index was calculated as ln[fasting triglycerides (mg/dL) * fasting glucose (mg/dL)/2]. Renal function decline was defined as >25% decline in estimated glomerular filtration rate (eGFR). The Cox proportional hazard regression model was used to examine the independent effect of the TyG index on renal events. In total, 548 Han Chinese hypertensive participants with a mean age of 62.1 ± 14.3 years were eligible for enrollment. During a mean follow‐up period of 4.7 ± 3.1 years, 97 patients suffered from >25% decline in eGFR. When compared to those without eGFR decline, patients with eGFR decline had higher fasting triglyceride levels (P = .056), fasting glucose levels (P = .014), and TyG indexes (P = .014). The Cox proportional hazard regression model revealed that the TyG index (hazard ratio [HR] = 1.490; 95% confidence interval [CI] = 1.016–2.185, P = .041), office systolic blood pressure (HR = 1.013; 95% CI = 1.000–1.026, P = .047), diabetes mellitus (HR = 1.797, 95% CI = 1.026–3.147, P = .040), and baseline eGFR (HR = 1.015; 95% CI = 1.002–1.028, P = .025) were associated with renal events. In conclusions, an elevated TyG index is independently associated with an increased risk of eGFR decline in hypertensive patients.